PENGARUH PEMBERIAN DNA EKSTRASELULER PADI (ORYZA SATIVA), PISANG CAVENDISH (MUSA ACUMINATA CAVENDISH AAA), DAN FUSARIUM OXYSPORUM F. SP. CUBENSE TROPICAL RACE 4 TERHADAP PRODUKSI H2O2 SERTA AKTIVITAS ENZIM ANTIOKSIDAN CAT DAN APX PADA KECAMBAH PADI - Ayu Intan Febrina W, Gusti
Plants often experience growth disturbances due to biotic and abiotic stresses. This necessitates the need for strategies to enhance plant defense mechanisms. Extracellular DNA has been found to have the potential to enhance plant defenses against biotic and abiotic stresses. Extracellular DNA refers to DNA that is located outside the cell and can be categorized as self or non-self based on its similarity to the recipient organism. Several studies have shown that both types of extracellular DNA have the ability to induce plant defense systems. The aim of this study was to compare the defense responses of rice seedlings treated with self and non-self extracellular DNA from Cavendish banana and FOC TR4 fungus. Self extracellular DNA was administered at two concentrations: 150 and 300 ng/?L. Non-self extracellular DNA was administered at a concentration of 300 ng/?L. Sterile deionized water was used as a control treatment for the rice seedling roots. The parameters examined in this study were the production of reactive oxygen species (ROS) in the form of H2O2, as well as the activities of the antioxidant enzymes catalase (CAT) and ascorbate peroxidase (APX) at 3, 6, 9, and 12 hours after treatment. The results of this study showed that all treatments involving the administration of self and non-self extracellular DNA increased the production of H2O2 and the activities of the antioxidant enzymes CAT and APX in the roots of rice seedlings. The administration of rice extracellular DNA at a concentration of 300 ng/?L resulted in the most significant increase in H2O2 production and the activities of the antioxidant enzymes CAT and APX across all treatment hours. A similar trend was observed with the administration of rice extracellular DNA at a concentration of 150 ng/?L, although the effects were not significant for one of the measured parameters, namely the activity of the antioxidant enzyme CAT at 3 and 6 hours. The administration of non-self extracellular DNA from bananas did not have a significant effect on most of the observed parameters, except for the APX enzyme activity at 3, 6, and 9 hours after treatment. Similarly, non-self extracellular DNA from FOC did not have a significant effect on any of the analyzed parameters or treatment hours. The study revealed that esDNA could exert its effects on the rice seedlings' roots without entering the tissues, while nsDNA could penetrate the root tissues. In conclusion, it can be inferred from this study that the administration of self and non-self extracellular DNA is capable of increasing H2O2 production and the activities of the antioxidant enzymes CAT and APX in the roots of rice seedlings. However, self extracellular DNA was found to have a greater influence on all tested parameters compared to non-self extracellular DNA.